Understanding the Effects of Product Quality and Brand Image on Customer Satisfaction and Loyalty in the Context of Muslim Fashion Retail - M. Wildan Nugraha; Kadir Kadir; Ashila Dwiyanisa; Tini Supartini (JURNAL COMPUTECH & BISNIS, 2026)
This research aims to analyze the influence of product quality and brand image on customer satisfaction and their impact on customer loyalty in a Muslim fashion company. Product quality and brand image are crucial factors in establishing long-term relationships with customers. Customer satisfaction is considered a mediator that affects customer loyalty, which is key to a company's success in an increasingly competitive market. This study employs a quantitative method, collecting data through questionnaires distributed to the customers of the Muslim fashion company under study. The findings indicate that product quality and brand image have a significant positive influence on customer satisfaction, and customer satisfaction positively impacts customer loyalty. These results underscore the importance of enhancing product quality and strengthening brand image to create satisfied and loyal customers within the Muslim fashion industry.